Displaying Cost and Completion Time for Reference Laboratory Test Orders—A Randomized Controlled Trial - Ikoma, Shohei; Pierce, Logan; Bell, Douglas S.; Cheng, Eric M.; Drake, Thomas; Guo, Rong; Ziman, Alyssa (Applied Clinical Informatics, 2022)
Objectives Reduction in unnecessary services is one strategy for increasing the value of health care. Reference laboratory, or send-out, tests are associated with considerable costs. We investigated whether displaying cost and turnaround time (TAT), or time-to-result, for reference laboratory tests at the time of order entry in the electronic health record (EHR) system would impact provider ordering practices.Methods Reference laboratory test cost and TAT data were randomized prior to the study and only displayed for the intervention group. A 24-month dataset composed of 12 months each for baseline and study periods was extracted from the clinical data mart. A difference-in-differences (DID) analysis was conducted using a linear mixed-effects model to estimate the association between the intervention and changes in test-ordering patterns.Results In the inpatient setting, the DIDs of aggregate test-order costs and volume were not different among the control and intervention groups (p = 0.31 and p = 0.26, respectively). In the ambulatory setting, the DIDs of aggregate test-order costs and volume were not different among the control and intervention groups (p = 0.82 and p = 0.51, respectively). For both inpatient and ambulatory settings, no significant difference was observed in the DID of aggregate test-order costs and volumes calculated in respect to stratified relative cost and TAT groups (p > 0.05).Conclusion Lack of alternative tests, test orders placed at a late step in patient management, and orders facilitated by trainees or mid-level providers may have limited the efficacy of the intervention. Our randomized study demonstrated no significant association between the display of cost or TAT display and ordering frequency.
Keywords: decision support; clinical; review; quality improvement